CoorSet: A Development Environment for Associatively Coordinated Components - Kane, Kevin; Browne, James C. (Coordination Models and Languages (COORDINATION 2004), 2004)
A development environment for applications specified in an extended version of a previously developed coordination model based on associatively broadcast interactions is presented. The previous associative broadcast coordination model is extended to incorporate more complex specifications for interactions including multiple message interactions and fault-tolerance by replication. The runtime system is extended to facilitate construction and application of distributed implementation of coordination systems. An interface definition language based on the extended coordination model and a compiler for the language are defined and described. Three example applications, a generalized readers/writers problem including replication, a ”greedy reuse” algorithm and a distributed computation of Google pageranks are presented.